Pregnancy hormones increase cardiac capillary density via the PGC-1α/ERRα/VEGF pathway in cardiomyocytes - Hesse, Michael; Korzus, Daniel; Thaben, Kristina; Wagner, Nicole; Ergün, Süleyman; Arany, Zoltan; Fleischmann, Bernd K. (Frontiers in Cardiovascular Medicine, 2025)
BackgroundPregnancy significantly affects the maternal cardiovascular system, with physiological adaptations characterized by cardiac hypertrophy and increased capillarization. However, the molecular mechanisms underlying these adaptations remain incompletely understood. Therefore, we analyzed them in mouse hearts at different stages of pregnancy and after hormone treatment. MethodsWe analyzed cell proliferation, capillary density, hypertrophy, and gene expression using immunostaining and quantitative RT-PCR to evaluate differential gene expression in mouse hearts at different stages during pregnancy and after treatment with combinations of progesterone and estrogen for up to 14 days. ResultsWe found that the number of proliferating cells in the hearts of pregnant mice began to increase at gestational day 3 (GD3), peaked at GD14—mainly in fibroblasts and endothelial cells (ECs), but not in cardiomyocytes (CMs)—and decreased immediately after delivery. EC proliferation was indicative of angiogenesis, as evidenced by increased capillary density. After hormone treatment, capillary density increased in the hearts of both female and male mice, without prominent CM hypertrophy and independently of nuclear hormone receptors. The proportion of proliferating cardiac cells and ECs was significantly increased after 14 days of treatment. Mechanistically, we identified activation of the PGC-1α/ERRα signaling pathway and upregulation of its downstream target VEGF-A. Using a CM-specific PGC-1α knockout mouse line, we demonstrated that the pregnancy hormone-induced angiogenesis is induced via PGC-1α signaling in CMs by secretion of VEGF.ConclusionsOur data indicated a direct effect of pregnancy hormones on cardiac capillarization, rather than indirect effects through CM hypertrophy, and demonstrate that capillary expansion is not sufficient to drive physiological hypertrophy. Pregnancy hormones directly act on CMs via the PGC-1α/ERRα signaling pathway and VEGF secretion, positioning CMs as a key source of angiogenic factors that promote endothelial cell proliferation and enhance capillary density in the heart.